DETERMINAN YANG MEMPENGARUHI NASABAH BANK SYARIAH INDONESIA DALAM PENGGUNAAN INTERNET BANKING - Nuraini Chaniago; Reviana Rahma Sari (Ekonomi Digital, 2022)
With the rapid development of computer technology as a commercial, Internet banking can also be used to attract more customers to conduct banking transactions at related banks. However, the main problem of Internet banking faced by providers is that a large number of bank customers are unwilling to use the offered Internet banking. This happens because the services offered through internet banking have not been able to satisfy their customers. Customer satisfaction is an important factor to help banks maintain a competitive advantage. Therefore, the purpose of this study is to find and examine the determinants that influence the use of Internet Banking services at Bank Syariah Indonesia. The design used is hypothesis testing with data collection techniques through questionnaires. In collecting data using a questionnaire and processed using the method of Structural Equation Modeling. The research variables consist of independent variables including the perception of convenience, the perception of trust, the perception of benefits and risks, while the interest in using Internet Banking as the dependent variable.